(untitled) (Vietnam Journal of Community Medicine, 2025)
Hue University of Medicine and Pharmacy, Hue University - 6 Ngo Quyen, Hue city, Thua Thien Hue province, Vietnam ABSTRACT Objectives: To describe knowledge and attitudes about research ethics among postgraduate students and their related factors. Method: This cross-sectional study was conducted by sefl-report randomly from 512 postgraduate students from the residents/master, specialist level 1, and specialist level 2 programs. The questionnaire was developed regarding national research ethics guidelines by the Ministry of Health to assess knowledge and attitude. Results: Our results revealed that most participants had a good knowledge of research ethics with mean of 14,8 ± 2,90, and median of 15,5. The mean attitude score was 73.2 ± 12.53 (range from 20-100). Prior research experience, major and year of training were associated with knowledge. In addition, a significant difference was observed between attitude toward research ethics and training programs and knowledge of research ethics. Conclusions: Pre-implementation of research ethics training, especially on informed consent and confidentiality in vulnerable groups, can be highly effective in protecting the rights of research subjects.